Continuous monitoring of stream δ18O and δ2H and stormflow hydrograph separation using laser spectrometry in an agricultural catchment. Issue 4 (15th October 2015) - Tweed, Sarah; Munksgaard, Niels; Marc, Vincent; Rockett, Nicholas; Bass, Adrian; Forsythe, Anthony J.; Bird, Michael I.; Leblanc, Marc
Abstract: A portable Wavelength Scanned‐Cavity Ring‐Down Spectrometer (Picarro L2120) fitted with a diffusion sampler (DS‐CRDS) was used for the first time to continuously measure δ 18 O and δ 2 H of stream water. The experiment took place during a storm event in a wet tropical agricultural catchment in north‐eastern Australia. At a temporal resolution of one minute, the DS‐CRDS measured 2160 δ 18 O and δ 2 H values continuously over a period of 36 h with a precision of ±0.08 and 0.5‰ for δ 18 O and δ 2 H, respectively. Four main advantages in using high temporal resolution stream δ 18 O and δ 2 H data during a storm event are highlighted from this study. First, they enabled us to separate components of the hydrograph, which was not possible using high temporal resolution electrical conductivity data that represented changes in solute transfers during the storm event rather than physical hydrological processes. The results from the hydrograph separation confirm fast groundwater contribution to the stream, with the first 5 h of increases in stream discharge comprising over 70% pre‐event water. Second, the high temporal resolution stream δ 18 O and δ 2 H data allowed us to detect a short‐lived reversal in stream isotopic values (δ 18 O increase by 0.4‰ over 9 min), which was observed immediately after the heavy rainfall period. Third, δ 18 O values were used to calculate a time lag of 20 min between the physical and chemical stream responses during the storm event. Finally, the hydrograph separation highlights the role of event waters in the runoff transfers of herbicides and nutrients from this heavily cultivated catchment to the Great Barrier Reef. Copyright © 2015 John Wiley & Sons, Ltd.